Use of syndromic surveillance data to monitor poisonings and drug overdoses in state and local public health agencies. (4th April 2016) - Ising, Amy; Proescholdbell, Scott; Harmon, Katherine J; Sachdeva, Nidhi; Marshall, Stephen W; Waller, Anna E
Abstract : Background: The incidence of poisoning and drug overdose has risen rapidly in the USA over the last 16 years. To inform local intervention approaches, local health departments (LHDs) in North Carolina (NC) are using a statewide syndromic surveillance system that provides timely, local emergency department (ED) and Emergency Medical Services (EMS) data on medication and drug overdoses. Objective: The purpose of this article is to describe the development and use of a variety of case definitions for poisoning and overdose implemented in NC's syndromic surveillance system and the impact of the system on local surveillance initiatives. Design, setting, participants: Thirteen new poisoning and overdose-related case definitions were added to NC's syndromic surveillance system and LHDs were trained on their use for surveillance purposes. Twenty-one LHDs were surveyed on the utility and impact of these new case definitions. Results/Conclusions: Ninety-one per cent of survey respondents (n = 29) agreed or strongly agreed that their ability to access timely ED data was vital to inform community-level overdose prevention work. Providing LHDs with access to local, timely data to identify pockets of need and engage stakeholders facilitates the practice of informed injury prevention and contributes to the reduction of injury incidence in their communities.